Impact of High-Altitude Hypoxia on Bone Defect Repair: A Review of Molecular Mechanisms and Therapeutic Implications - Chen, Pei; Liu, Yushan; Liu, Wenjing; Wang, Yarong; Liu, Ziyi; Rong, Mingdeng (Frontiers in Medicine, 2022)
Reaching areas at altitudes over 2500-3000 meters above sea level had become more common than before due to commerce, military deployment, tourism and entertainment. The high altitude environment exert systemic effects on humans that represent a series of compensatory reactions and affected the activity of bone cells. Cellular structures closely related to oxygen sensing produced corresponding functional changes, resulting in decreased tissue vascularization, declined repair ability of bone defects and longer healing time. This review focused on the the impact of high altitude hypoxia on bone defect repair and discussed the possible related mechanisms in ion channels, reactive oxygen species(ROS) production, mitochondrial function, autophagy and epigenetics. Based on the key pathogenic mechanisms, potential therapeutic strategies had been suggested. It contributed novel insights into the mechanisms of abnormal bone defect repair in the hypoxia environment and therapeutic applications. It was hoped that this review will provide a reference basis for future targeted, personalized and precise bone regeneration methods that can be adjusted according to patients' adaptation to high altitude.